Analysis and Simulation of the Couple Direct Kinematics of a Six Wheeled Mobile Platform with a 3 DOF Manipulator Arm - Cristian H. Muñoz García, Oscar F. Avilés Sánchez, Mauricio F. Mauledoux Monroy (International Journal of Advanced Science and Technology, 2020)
This paper presents the Couple Direct Kinematics (CDK) done for the Manipulator Mobile Robot VALI 3. This robot has 6 standard wheels and a 3 (Degrees of Freedom) DOF manipulator arm in which all the joints are rotational. This analysis was divided in 3 steps, the first step was the manipulator arm’s Direct Kinematics (DK) analysis; the second step was finding the mobile platforms DK at its Geometric Center (GC) and how to find the manipulator arms base DK. The third step was coupling the manipulator arm and mobile platform’s DK into the VALI 3’ CDK. Three different trajectories were simulated using Matlab® and Simulink in order to verify the CDK analysis previously done. These trajectories were a sine function, cubic function, and a 3/4 circle ending with a trajectory for the manipulator arm’s end effector. Keywords: Manipulator Arm, Mobile Platform, Couple Direct Kinematics, Standard Wheels, Slipping Restrictions, Planned Trajectories.